2019
DOI: 10.1007/s11051-019-4631-1
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and biodegradation of zinc ferrite nanoparticles in Xenopus laevis

Abstract: Zn-doped Fe3O4 magnetic nanoparticles have been proposed as the ideal ferrite for some biomedical applications like magnetic hyperthermia or photothermal therapy because of the possibility to adjust their size and chemical composition in order to design tailored treatments. However, reliable approaches are needed to risk assess Zn ferrite nanoparticles before clinical development. In this work, the in vitro toxicity of the nanoparticles was evaluated in five cellular models (Caco-2, HepG2, MDCK, Calu-3 and Raw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
3
6
0
Order By: Relevance
“…This fingerprint signal was in agreement with previously described results for mouse ferritin measured in similar conditions and for ferritin from other mammals such as rats or horses . Indeed, similar signals, located at slightly lower temperatures have also been described for ferritins coming from Xenopus laevis or Drosophila melanogaster …”
Section: Resultssupporting
confidence: 92%
“…This fingerprint signal was in agreement with previously described results for mouse ferritin measured in similar conditions and for ferritin from other mammals such as rats or horses . Indeed, similar signals, located at slightly lower temperatures have also been described for ferritins coming from Xenopus laevis or Drosophila melanogaster …”
Section: Resultssupporting
confidence: 92%
“…Comparing our viability results with previous studies in which mixed ferrite nanoparticles were employed is not straightforward, because often, the nanoparticles chosen for those studies differ in size, composition, shape and coatings, all parameters affecting nanoparticle behavior in cell media thus their cytotoxicity on chosen cancer cell lines. [65][66][67][68] The cell viability findings with our Zn-ferrite NCs are in line with Zn-ferrite nanoparticles prepared by the electrochemical method, with a spherical shape, similar size (13 nm) and similar non-stoichiometry composition (Zn 0.5 Fe 2.5 O 4 ), and administered at a similar nanoparticle dosage. 65 For the Co-ferrite NCs, at 100 nM and after 72 h, the cell morphology looked altered, with membrane blabbing and clear signs of cell suffering.…”
Section: Characterization Of Ferrite Ncs For Magnetic Hyperthermia Mri and Mpi Applicationssupporting
confidence: 72%
“…In the in vivo study, abnormal phenotypes were identified, with swollen and deformed gastrointestinal tracts. At short term exposure of 72 h predominant absorption of NPs was observed, with overexpression of metal response proteins and metal transporters, whereas after long term exposure of 120 h the upregulated genes involved in metal accumulation returned to basal levels for both iron and zinc in the body, which primarily suggests that at the long term exposure stage, the nanoparticle absorption process is much less because of underlying processes of metabolism, distribution and excretion [ 152 ].…”
Section: Mnp Toxicity In Vitro and In Vivomentioning
confidence: 99%